Langqing Meiduo Jiujie pills treatment attenuates acute liver injury in animals by regulating anti-oxidative stress and liver metabolism - Zhongyuan Wang; Zhongyuan Wang; Fangjie Wang; Fangjie Wang; Yan Huang; Yan Huang; Gebai Zhaxi; Jiaqing Fu; Jiaqing Fu; Guili Song; Guili Song; Bai Bai; et al. (Frontiers in Pharmacology)
IntroductionLangqing Meiduo Jiujie pills (LQMDJJP), a Tibetan formula, has a history of more than 400 years of clinical use. However, there has been no report on the scientific basis of its dosage or its mechanism of action in treating acute liver injury. To investigate the optimal clinical dosage of LQMDJJP, to examine the differences in differential metabolites in liver tissue following treatment with LQMDJJP, and to explore the mechanism through which LQMDJJP acts in the treatment of acute liver injury.Materials and MethodsHE staining was used to observe the pathological changes of the liver, and the Suzuki pathological score was counted. The levels of ALT (Alanine aminotransferase), AST (Aspartate aminotransferase), TBIL (Total bilirubin), DBIL (Direct bilirubin), SOD (Superoxide dismutase), MDA (Malondialdehyde), GSH (Glutathione) and GSSG (Glutathione disulfide) and were detected by colorimetry kit. UPLC-Q-TOF-MS metabolomics technology was used to explore the differential metabolites and differential metabolic pathways of LQMDJJP in the treatment of acute liver injury. PCR and WB were employed to confirm the mechanism of LQMDJJP in treating acute liver injury via the Keap1-Nrf2 to anti-oxidative stress pathway.ResultsThis study found that the optimal dose of LQMDJJP in the treatment of C57BL/6 mice was 333.33 mg/kg/d, and the optimal dose of LQMDJJP in the treatment of SD rats was 166.66 mg/kg/d. It was found that LQMDJJP can improve the morphological state and pathological changes of the liver, significantly reduce the levels of ALT, AST, TBIL, DBIL, SOD and GSH, and also increase the levels of MDA and GSSG. UPLC-Q-TOF-MS metabolomics technology screened 121 metabolic differences and six metabolic pathways that met the screening conditions. It was found that the treatment of acute liver injury by LQMDJJP may be related to the metabolism of glutamic acid, glutamine and γ-glutamylalanine. LQMDJJP can reduce the gene and protein expression levels of Keap1 and can increase the gene and protein expression levels of Nrf2, HO1, NQO1, GCLC and other oxidative stress indicators.DiscussionLQMDJJP can significantly improve acute liver injury induced by CCl4 and APAP, and the clinical dosage is reasonable, and its protective effect against APAP-induced acute liver injury is mediated through the Keap1-Nrf2 to anti-oxidative stress mechanism.